2018
DOI: 10.7759/cureus.3776
|View full text |Cite
|
Sign up to set email alerts
|

Ceftaroline Fosamil as an Alternative for a Severe Methicillin-resistant Staphylococcus aureus Infection: A Case Report

Abstract: Bacteremia secondary to methicillin-resistant Staphylococcus aureus (MRSA) is a dreaded medical condition that is not only associated with a significant medical cost but also carries high morbidity and mortality. The poor clinical outcomes seen in MRSA patients and the nephrotoxic effects of high-doses of vancomycin are challenging its current status as the first-line treatment for MRSA. Fortunately, vancomycin-intermediate-staphylococcus aureus (VISA) and vancomycin-resistant-staphylococcus aureus (VRSA) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Pulmonary MRSA and MRSE infections are types of antimicrobial-resistant infections that are common in our hospital and are associated with shock, ventilator use, invasive surgeries, and anesthesia. Most patients with these infections experience some degree of dyspnea, fever, expectoration, and other manifestations[ 12 , 13 ]. Moreover, the incidence of pulmonary infections caused by MRSA and MRSE has continued to increase over recent years due to the increasing frequency of antibiotic misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary MRSA and MRSE infections are types of antimicrobial-resistant infections that are common in our hospital and are associated with shock, ventilator use, invasive surgeries, and anesthesia. Most patients with these infections experience some degree of dyspnea, fever, expectoration, and other manifestations[ 12 , 13 ]. Moreover, the incidence of pulmonary infections caused by MRSA and MRSE has continued to increase over recent years due to the increasing frequency of antibiotic misuse.…”
Section: Discussionmentioning
confidence: 99%
“…However, its activity against Gram-negative pathogens is limited, with no efficacy against extended-spectrum β-lactamase (ESBL)producing or the AmpC-overexpressing Enterobacteriaceae. 6…”
Section: The Emergence Of Ceftaroline Fosamilmentioning
confidence: 99%
“…Few single-centre observational studies reported positive clinical and/or microbiological outcomes in MRSA BSI populations, with or without specific data on the IE subgroups [70][71][72][73][74][75][76]. Additionally, several case series and complicated case reports showed microbiological cure and clinical success in IE patients treated with CPT as a monotherapy or in combination [56,72,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Clinical Evidence In Infective Endocarditismentioning
confidence: 99%